Analysis of the Effect Current Ratio on Return on Assets at PT Astra Otoparts TBK - Ikhyanuddin Ikhyanuddin; Fatma Sarie; Andi Aris Mattunruang; Eva Yuniarti Utami; Fajriani Azis (Global Research Collaboration, 2023)
This study makes an important contribution in understanding the relationship between current ratio and return on assets at PT Astra Otoparts Tbk. Through the use of a simple linear regression test on financial statement data for the period 2015-2022, this study intends to explain the extent to which the current ratio affects the company's return on assets. Current ratio, as the independent variable, is used as an indicator of the company's ability to meet its short-term obligations, while return on assets, as the dependent variable, reflects the company's level of profitability. The results show that, although the current ratio has a positive influence on return on assets, the influence is not statistically significant. In other words, the increase in current ratio does not contribute significantly to the increase in return on assets at PT Astra Otoparts Tbk. The findings can provide valuable insights for company management in designing financial strategies, especially in terms of managing short-term assets and liabilities. In the context of the automotive and spare parts industry in Indonesia, where PT Astra Otoparts Tbk operates, an in-depth understanding of the factors that influence return on assets is crucial. The results of this study can serve as a basis for similar companies to evaluate and improve their financial performance, optimize asset allocation, and manage short-term liabilities more effectively. Further research and the integration of other factors in financial analysis can help shape a more holistic and sustainable business strategy amidst changing market dynamics.